Measurements of production cross sections of WZ and same-sign WW boson pairs in association with two jets in proton-proton collisions at vs=13TeV; Physics Letters B; Vol. 809 - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Bergauer T. Thomas; Zhokin A. S. Aleksandr Sergeevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich; Sukhikh L. G. Leonid Grigorievich (2020, 2020)
Title screen